Human Rights and Corruption in the Perspective of Law Number 39 of 1999, Jo Law Number 21 of 2001 concerning the Eradication of Corruption - Nasution, Ingka Harsani (Ann Publisher, 2025)
Background. Corruption is a crime that has a multidimensional impact and hinders national development. As a crime that has caused leakage of state finances, corruption threatens the fulfillment of citizens' basic rights, especially economic, social, and cultural rights. Purpose. This study aims to understand the basis of judges' considerations in imposing a penalty, including the death penalty, and to analyze whether corruption can be categorized as a violation of Human Rights (HAM). Method. With a juridical-normative method through the analysis of laws and regulations, doctrines, and literature Result. This study found that corruption has the characteristics of extra-ordinary crimes and substantially impacts human rights violations, especially when corruption causes a loss of people's access to welfare. Conclusion. This research confirms that national legal mechanisms need to recognize corruption as a serious human rights violation.